Studies on Homalomeneae (Araceae) of Borneo VII: Homalomena debilicrista, a new species from Malaysian Borneo, and observations of its pollination mechanics - Chen, Hoe Yin; Wong, Sin Yeng; Boyce, P.C; Hung, Wong Mui; Yok, Margaret Chan Kit (Publishing Technology, 2011)
Homalomena debilicrista Y.C.Hoe is described and illustrated as a species new to science from the Matang massif sandstone formation, Kuching Division, NW Sarawak, Malaysian Borneo. It represents the sixth species of the informal Hanneae Complex, a morphotaxon apparently endemic to Borneo and composed wholly of nomenclaturally novel species. Inflorescence events, notably spathe movement mechanisms, and interactions with insect visitors were observed and recorded to determine pollinator/s as part of an on-going programme accumulating data on pollinator guild niche partitioning in Homalomena. Six insect taxa visited the inflorescences during anthesis: (1) Coleoptera — Chrysomelidae (Chaloenus schawalleri), Scarabaeidae: Rutelinae (Parastasia bimaculata), Nitidulidae (genus undetermined), and Staphylinidae (genus undetermined) - and (2) Diptera, two species of Colocasiomyia (Drosophilidae). Empirical data strongly implicate P. bimaculata and possibly C. schawalleri to be the pollinators of Homalomena debilicrista. A key to the so-far described species of the Homalomena Hanneae Complex is presented, and the new species is illustrated.